2013
DOI: 10.1152/ajpendo.00080.2013
|View full text |Cite
|
Sign up to set email alerts
|

The eukaryotic initiation factor 2 kinase GCN2 protects against hepatotoxicity during asparaginase treatment

Abstract: Asparaginase is an important drug in the treatment regimen for acute lymphoblastic leukemia. Asparaginase depletes circulating asparagine and glutamine, activating an amino acid stress response (AAR) involving phosphorylation of eukaryotic initiation factor 2 (eIF2) by general control nonderepressible kinase 2 (GCN2). We hypothesized that GCN2 functions to mitigate hepatic stress during asparaginase therapy by activating the AAR. To test this idea, C57BL/6J wild-type mice (Gcn2(+/+)) and those deleted for Gcn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 60 publications
11
47
0
Order By: Relevance
“…This suppressive role of GCN2 was first observed by us in mice fed a leucine devoid diet to Gcn2 -/-mice (10), then confirmed and further detailed using mice treated with asparaginase (8,9,19,25). This work also strongly supports the findings of Averous et al who used a model of leucine deprivation in mouse embryonic fibroblasts (MEFs) (20) to conclude that GCN2 and eIF2 phosphorylation, but not ATF4, are required for continuous suppression of mTORC1 during leucine or arginine deprivation.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This suppressive role of GCN2 was first observed by us in mice fed a leucine devoid diet to Gcn2 -/-mice (10), then confirmed and further detailed using mice treated with asparaginase (8,9,19,25). This work also strongly supports the findings of Averous et al who used a model of leucine deprivation in mouse embryonic fibroblasts (MEFs) (20) to conclude that GCN2 and eIF2 phosphorylation, but not ATF4, are required for continuous suppression of mTORC1 during leucine or arginine deprivation.…”
Section: Discussionsupporting
confidence: 61%
“…Notably, asparagine concentrations were consistently reduced over time whereas glutamine concentrations were acutely reduced at 3 h post injection which then recovered to serum levels in untreated mice by 12 h ( Figure S1). Circulating levels of most other amino acids and in particular the dietary essential amino acids steadily increased over 24 h ( Figure S2) (9). Activation states of GCN2 and mTORC1 were tracked by assessing phosphorylation of their respective substrates, eIF2 and S6K1, respectively.…”
Section: Loss Of Gcn2 Quickly Unleashes Hepatic Mtorc1 Activity Durinmentioning
confidence: 99%
See 1 more Smart Citation
“…4 According to our results, we can hypothesize that MMC depletes GCN2 in the lungs and mimics PVOD induced by EIF2AK4 mutations. Interestingly, Wilson et al 37 have demonstrated that the loss of GCN2 promotes oxidative stress and inflammatory-mediated DNA damage during asparaginase therapy; this suggests that patients with reduced GCN2 may be at risk of developing hepatic complications during asparaginase treatment. Our results may suggest that MMC-induced GCN2 depletion could favor similar oxidative and inflammatory pulmonary injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from our laboratory and others demonstrate that mice deleted for Gcn2 fail to phosphorylate eIF2 during both dietary and pharmaceutical amino acid deprivation, resulting in hepatic steatosis and liver injury (2,12,24,43,50). Depletion of circulating asparagine and glutamine is accomplished by asparaginase (37,39), an effective tumor killing agent in patients diagnosed with acute lymphoblastic leukemia.…”
mentioning
confidence: 99%